The traditional Chinese formulae Ling-gui-zhu-gan decoction alleviated non-alcoholic fatty liver disease via inhibiting PPP1R3C mediated molecules - Yanqi Dang; Shijun Hao; Wenjun Zhou; Li Zhang; Guang Ji (BMC, 2019)
Abstract Background Ling-gui-zhu-gan decoction (LGZG), a classic traditional Chinese medicine formula, has been confirmed to be effective in improving steatosis in non-alcoholic fatty liver disease (NAFLD). However, the mechanism under the efficacy remains unclear. Hence, this study was designed to investigate the mechanisms of LGZG on alleviating steatosis. Methods Twenty four rats were randomly divided into three groups: normal group, NAFLD group, fed with high fat diet (HFD) and LGZG group (fed with HFD and supplemented with LGZG). After 4 weeks intervention, blood and liver were collected. Liver steatosis was detected by Oil Red O staining, and blood lipids were biochemically determined. Whole genome genes were detected by RNA-Seq and the significant different genes were verified by RT-qPCR. The protein expression of Protein phosphatase 1 regulatory subunit 3C (PPP1R3C) and key molecules of glycogen and lipid metabolism were measured by western blot. Chromophore substrate methods measured glycogen phosphorylase (GPa) activity and glycogen content. Results HFD can markedly induce hepatic steatosis and promote liver triglyceride (TG) and serum cholesterol (CHOL) contents, while liver TG and serum CHOL were both markedly decreased by LGZG treatment for 4 weeks. By RNA sequencing, we found that NAFLD rats showed significantly increase of PPP1R3C expression and LGZG reduced its expression. RT-qPCR and Western blot both verified the alteration of PPP1R3C upon LGZG intervention. LGZG also promoted the activity of glycogen phosphorylase liver type (PYGL) and inhibited the activity of glycogen synthase (GS) in NAFLD rats, resulting in glycogenolysis increase and glycogen synthesis decrease in the liver. By detecting glycogen content, we also found that LGZG reduced hepatic glycogen in NAFLD rats. In addition, we analyzed the key molecules in hepatic de novo lipogenesis and cholesterol synthesis, and indicated that LGZG markedly inhibited the activity of acetyl-CoA carboxylase (ACC), sterol receptor element-binding protein-1c (SREBP-1c) and 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), resulting in lipid synthesis decrease in the liver. Conclusion Our data highlighted the role of PPP1R3C targeting pathways, and found that hepatic glycogen metabolism might be the potential target of LGZG in preventing NAFLD.